2011
DOI: 10.1080/10410236.2011.561919
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bad News: The Patient's Viewpoint

Abstract: The objective of this study was to ascertain how patients judge the acceptability of physicians' communication of bad news. Two hundred forty-five adults, who had in the past received bad medical news, indicated the acceptability of physicians' conduct in 48 vignettes of giving bad news to patients. Vignettes were all combinations of five factors: level of bad news (infection with hepatitis C, cirrhosis of the liver, or liver cancer); request or not to the patient to come with spouse or partner; attempt or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…Physicians need to accept that patients expect high levels of both empathy and information quality, no matter how bad the news is [13]. Kübler-Ross pointed out that patients usually know the bad news about upcoming death, regardless of whether they are informed by the physician.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians need to accept that patients expect high levels of both empathy and information quality, no matter how bad the news is [13]. Kübler-Ross pointed out that patients usually know the bad news about upcoming death, regardless of whether they are informed by the physician.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis on the expected functional state and quality of life as well as emotional support have been shown to be the real need of patient and family [13-15]. Sastre et al [16]. assert that support cannot be fully compensated by high quality of information, which is the contrary to the thesis popular among physicians for whom such a compensation is possible.…”
Section: Reviewmentioning
confidence: 99%
“…12,13,15,16 The quality and completeness of information coupled with the physician's emotional support were considered important factors in breaking bad news appropriately in another study in France. 17 Alternatively, the process of a patient's understanding of the bad news is complex. Morse concluded that being told bad news is only one part of the patient's knowing.…”
mentioning
confidence: 99%